THE ROLE OF BANKS IN THE DEVELOPMENT OF THE REAL SECTOR ECONOMY OF UZBEKISTAN (World Economics and Finance Bulletin, 2023)
The article examines the role of the banking sector in the development of some sectors of the real sector of the economy of Uzbekistan. The role of the functioning of the banking sector and its capabilities are determined. The influence of commercial banks' activities on the innovative development of some branches of the real sector of the economy is analyzed. And also developed proposals and recommendations on the integration prerequisites of commercial banks and their support of the real sector.